Prolonged Labor Incidences: Passage-Passenger Factors Analyzed: Descriptive Study in RSUD dr. Koesma Tuban - Santi, Dwi Rukma; Pribadi, Eko Teguh (International Conference on Sustainable Health Promotion, 2018)
Prolonged labor is parturition that lasts more than 24 hours, also the last phase of employment that is congested and lasts too long which evoke symptoms such as dehydration, infection, maternal fatigue, asphyxia and fetal death in the uterus. Several determinants factors include power, passage, passenger and helper (physician). The research purpose was to describe the elements behind the prolonged labor incidences regarding adoption and passenger. This research is a descriptive study that aims to make an overview of the prolonged labor incidences at RSUD dr. Koesma Tuban in the period of 2015-2016. Data collection was obtained through secondary data which is medical records of patients who experienced prolonged labor. The results showed that 143 patients experience a prolonged labor, 47.55% types of prolonged labor was prolonged active phase, 41.6% types of labor was Caesarean Section (SC), 65.04% of outer pelvis were normal, 57, 34% had no CPD (Cephalopelvic Disproportion), 58.74% with soft birth abnormalities, 82.52% babies born were between 2500-4000 grams, and 80.42% of the fetus was in the normal position (vertex presentation). The possibility of prolonged parturition should be anticipated by routine pregnancy examinations so that the condition of the mother and fetus continuously monitored.